In Vivo Evaluation on Synbiotic Effect of Fermented Rice Bran by Probiotic Lactic Acid Bacteria (Lactobacillus plantarum B2 and Lactobacillus casei) - Nurcholis, Mochamad; Zubaidah, Elok (Fakultas Teknologi Pertanian Universitas Brawijaya, 2011)
Rice bran contains dietary fiber such as hemicellulose, arabinogalactan, arabinoxylan, xylogycan, proteoglycan, arabinofuranoside, and raffinose. Those dietary fibers have a potency as prebiotic and to be fermented by probiotic in colon to produce lactic acid and short chain fatty acid (SCFA). Synbiotic effect of fermented rice bran by Lactobacillus plantarum B2 and Lactobacillus casei on Wistar rats (Rattus norvegicus) was investigated. Â A two month old Wistar rats (Rattus norvegicus) consisted of four groups (F0, F1, F2, F3) with five rats of each group were adapted for ten days by giving standard diet (AIN-93). There were four diet formulas: standard diet of AIN 93 M (F0), standard diet with formulated rice bran media (F1), standard diet with fermented rice bran media by L. casei (F2) and standard diet with L. plantarum B2 (F3). The weight, LAB viability, pH, and total acid of rat faecal were measured in 20 days. SCFA production was measured after 20 days experiment. Data were analyzed using ANOVA (Î±=5%) and least significant difference (Î±=5%). The best treatment was obtained using ranking method. Â F3 was the best treatment with fecal LAB viability of 5.8x107 CFU/g, faecal pH of 6.47 on 20th day experiment, caecum LAB viability of 6.77x108 CFU/g, caecum total acid of 0.20% lactic acid, caecum pH of 6,34, and SCFA total of 11.49 mg/g (acetic acid of 7.11 mg/g, propionic acid of 3.03 mg/g and butyric acid of 1.35 mg/g).Keywords: synbiotic, rice bran, probiotic, SCFA, wistar rat